磁気嵐時におけるグローバル地磁気変動 - 新堀, 淳樹; 西村, 幸敏; 辻, 裕司; 菊池, 崇; 長, 妻努; 亘, 慎一; Atsuki, Shinbori; Yukitoshi, Nishimura; Yuji, Tsuji; Takashi, Kikuchi; Tsutomu, Nagatsuma; Shinichi, Watari (2010)
第34回極域宙空圏シンポジウム 12月3日（金） 国立極地研究所 2階大会議室 conference object